2015
DOI: 10.1002/prot.24794
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the C-terminal 2′,5′-phosphodiesterase domain of group a rotavirus protein VP3

Abstract: In response to viral infections, the mammalian innate immune system induces the production of the second messenger 2'-5' oligoadenylate (2-5A) to activate latent ribonuclease L (RNase L) that restricts viral replication and promotes apoptosis. A subset of rotaviruses and coronaviruses encode 2',5'-phosphodiesterase enzymes that hydrolyze 2-5A, thereby inhibiting RNase L activation. We report the crystal structure of the 2',5'-phosphodiesterase domain of group A rotavirus protein VP3 at 1.39 Å resolution. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…1A and 2C). This finding is consistent with a recently reported structure for the VP3 CTD of another simian RVA (strain SA11) (34). The two H⌽(S/ T)⌽ motifs, consisting of H718, L719, T720, and F721 from the ␤2-strand and H797, I798, T799, and L800 from the ␤5-strand, are located adjacent to one another at the base of the catalytic cleft.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1A and 2C). This finding is consistent with a recently reported structure for the VP3 CTD of another simian RVA (strain SA11) (34). The two H⌽(S/ T)⌽ motifs, consisting of H718, L719, T720, and F721 from the ␤2-strand and H797, I798, T799, and L800 from the ␤5-strand, are located adjacent to one another at the base of the catalytic cleft.…”
Section: Resultssupporting
confidence: 92%
“…In the apo VP3 CTD crystal structure, the R loop and R792 exhibit significantly different positioning and side chain orientation than those of apo AKAP7. This is also true for the apo VP3 CTD structure of RVA strain SA11 (34). To engage the base of the 5= adenosine and the phosphate moieties of the second adenosine, this loop changes conformation and moves toward the substrate and catalytic site by several angstroms (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…It is a multi-functional capping enzyme of 835 amino acids [65]. While the N-terminal region of~690 residues contains domains needed for mRNA capping functions (a variable N-terminal domain, a guanine-N7-methyltransferase (N7-MTase) domain, a ribose-2 0 -O -methyltransferase domain, a guanylyltransferase and RNA 5 0triphosphatase (GTPase/RTPase) domain), the C-terminal region of~150 amino acids possesses a 2 0 ,5 0 -phosphodiesterase (PDE) activity that cleaves 2 0 -5 0 -oligoadenylate [66,67], thereby preventing RNase L activation [66,67]. Apart from capping-associated activities, VP3 is also associated with virulence.…”
Section: Structural Protein Vp3mentioning
confidence: 99%
“…In its N7-MTase and GTase/RTPase domains, VP3 has some sequence motifs that are conserved among the rotavirus and orbivirus species. The conserved residues in the N7-MTase domain are located in region 134-139, whereas in GTase/RTPase domain, residues from 552 to 555 and Ser527, Arg531, Trp571, His610 are highly conserved [66,67]. Even though this multifunctional protein has a mean PPID score of 0% {Table 1}, individual predictors, such as PONDR Ò VLXT, PONDR Ò VSL2, and PONDR Ò FIT have predicted short stretches of Table 2 MoRF analysis of all proteins of SA11 rotavirus strain by four different tools.…”
Section: Structural Protein Vp3mentioning
confidence: 99%
“…2a). The structures of AKAP7 CD (PDB ID 2VFY) and VP3-CTD (PDB ID 5AF2), which exhibit substantial structural homology, have previously been determined (Brandmann & Jinek, 2015;Ogden et al, 2015). The structural alignment of ns2 7-167 , AKAP7 CD and VP3-CTD indicated that all of these structures form similar positive electrostatic concave regions in the 29,59-PDE activity domain, which is putatively involved in the binding and cleavage of 2-5A ( Fig.…”
mentioning
confidence: 96%